Different Modalities and Parameters in Spinal Cord Stimulation Treatment - Cai, Jiacheng; Zheng, Zhide (Transactions on Computer Science and Intelligent Systems Research, 2024)
Electrical stimulation to treat diseases can be tranced back to the pharaonic era. Since then, people have found using the electrical pulse generated by electric cat-fish can mange the patient’s pain effectively. Foreign studies started early, and the technology was relatively mature. Spinal cord stimulation was produced in the 1960s by inserting stimulating electrodes into the spinal canal’s epidural area. At the same time, the pulse generator was implanted subcutaneously to achieve the purpose of pain treatment with electrical pulses. This article will introduce three main types of stimulation mechanism: constant voltage stimulation, constant current stimulation and activation of the charge mode. Compare the impact of the given stimulus with the design’s complexity. However, because the electrode impedance varies with position and time, it is difficult to precisely control the charge of the stimulus, resulting in difficulty in controlling the net charge balance. Secondly, introduce the different parameters and their role in spinal cord stimulation, including the threshold of the cell membrane decide if it can generate the action potential. And the relationship between stimulation amplitude and pulse width, the current intensity is gradually reduced with the grow of stimulation pulse width. And the frequency and waveform, these parameters influence each other and are considered as the most important factors for the patients’ pain management in SCS.